The Experience of Distant Teaching a Foreign Language to Engineering Students during the COVID-19 Pandemic - Olga V. KARCHAVA; Tatyana N. KURENKOVA; Tatyana V. STREKALEVA (Communications of International Proceedings, 2021)
The article describes the experience of distant teaching a foreign language to engineering students at Reshetnev Siberian State University of Science & Technology. The main features of the interaction of the students with each other and with the teachers during the educational process using the server of distant learning are revealed and shown. Since Reshetnev Siberian State University of Science & Technology uses the Moodle software for distant learning, the authors have described the main characteristics and advantages of this digital educational resource. Eight key advantages are given in the context of the prospects for using automated systems based on artificial intelligence technologies in teaching foreign languages. The authors of the article have noted some negative influence of modern computer technologies on the process of teaching a foreign language at a higher educational institution as well.